The Influence of Leadership, Work Environment, and Or-ganizational Culture on Employee Performance at PERUM DAMRI Bandar Lampung City - Erwansyah Erwansyah; Andi Surya; M.Renandi Ekatama Surya; Armalia Reny; Megasari Megasari; Desmon Desmon; Susi Indriyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine and analyze whether leadership, work environment and organizational culture have a joint influence on employee performance at Perum Damri Bandar Lampung City. The type of data in this study uses quantitative research using primary and secondary data. The sample used is Non-Probability Sampling with saturated sampling type. With a sample of 60 employees who work as office staff at Perum Damri Bandar Lampung City. The analysis technique used is through validity, reliability, classical assumptions and hypothesis tests. From the results of the research that has been done shows that Leadership has an influence and is significant on Employee Performance with an influence contribution of 26.1%. Work Environment has an influence and is significant on Employee Performance with an influence contribution of 25.7%. Organizational Culture has an influence and is significant on Employee Performance with an influence contribution of 37.3%. Leadership, Work Environment and Organizational Culture have a simultaneous and significant influence on Employee Performance at Perum Damri Bandar Lampung. Leadership, Work Environment and Organizational Culture have an influence and are significant on Employee Performance at Perum Damri Bandar Lampung by 89.1%. The remaining 10.9% is influenced by other factors not examined in this study.